(untitled) (Revista Venezolana de Salud Pública, 2018)
We arrived at the second issue of the Revista Venezolana de Salud Pública (RVSP), thanking all our readers for the enormous reception this journal has received, mainly in professionals and students of the Health Sciences, both national and foreign, acceptance that is evident in the more than two thousand consultations per month.